Streptomycin- and rifampin-resistant mutants of Escherichia coli perturb F exclusion of bacteriophage T7 by affecting synthesis of the F plasmid protein PifA. - Schmidt, C K (1995)
Certain alleles of rpsL that confer resistance to the antibiotic streptomycin almost completely relieve F exclusion of bacteriophage T7. Introduction of a specific rpoB allele conferring resistance to rifampin into the rpsL strain restores the ability of the F-containing strain to exclude T7. This variation in the severity of F exclusion is reflected in the levels of the F-encoded inhibitor protein PifA: F'-containing cells that harbor specific rpsL alleles are phenotypically Pif-, but become Pif+ by the further acquisition of a specific rpoB allele. F-containing cells harboring the gyrA43(Ts) mutation also appear phenotypically Pif-, possibly because repression of the pif operon is enhanced by an altered DNA conformation in the gyrase mutant strain.